2016
DOI: 10.1007/s10120-016-0631-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of programmed death ligand 1 expression with tumor-infiltrating lymphocyte, mismatch repair, and Epstein–Barr virus status in a large cohort of gastric cancer patients

Abstract: In GC, PD-L1 expression was associated with distinct clinicopathological features, including high densities of TILs, MMR deficiency, and EBV positivity, but was not a prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
159
6
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(197 citation statements)
references
References 22 publications
16
159
6
16
Order By: Relevance
“…A review of the investigation of TILs I gynecologic cancers revealed that most of the cases that had positive intramural CD3/ CD8 had better chemotherapeutic and/or surgical outcomes [17], supporting an effective interaction between the host's immune system and cancer. Additionally, a report on gastric cancers revealed that programmed cell death-1 ligand 1-positive tumors had an increased density of TILs, and were frequently observed in mismatch repair deficiency subtype [18]. Although detailed mechanisms are still undetermined, TILs and zone formation of LI could be associated with immune response in the host and inverse effects for prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the investigation of TILs I gynecologic cancers revealed that most of the cases that had positive intramural CD3/ CD8 had better chemotherapeutic and/or surgical outcomes [17], supporting an effective interaction between the host's immune system and cancer. Additionally, a report on gastric cancers revealed that programmed cell death-1 ligand 1-positive tumors had an increased density of TILs, and were frequently observed in mismatch repair deficiency subtype [18]. Although detailed mechanisms are still undetermined, TILs and zone formation of LI could be associated with immune response in the host and inverse effects for prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that PD-L1 immunoexpression is heterogeneous in GC, as in other tumour models. PD-L1 overexpression is associated with high densities of CD3+ and CD8+ tumour-infiltrating lymphocytes [67][68][69], GC with lymphoid stroma morphology [70], and both an EBV+ and MSI-high molecular status [69,[71][72][73][74]. However, the correlation with PD-L1 amplification, prognosis, and response to targeted immunotherapies is still debated and deserves further study.…”
Section: Moving Towards Molecular Subtyping and Precision Medicinementioning
confidence: 99%
“…PD‐L1 and PD‐L2 ligate the inhibitory T‐cell receptor PD‐1, which abrogates the T‐cell‐mediated immune response . Overall, 25‐65% of all gastric cancers express PD‐L1, which is associated with worse pathologic features and clinical outcomes . Patterns of PD‐L1 expression on tumor and immune cells and density of the immune infiltrate is associated with T category, rate of lymph node metastasis, and disease‐free survival, however, these findings require further confirmation.…”
Section: Biologic Rationale For Immunotherapy Efficacy In Gastric Canmentioning
confidence: 99%
“…PD‐L1 is a co‐inhibitory molecule expressed on the surface of tumor‐infiltrating macrophages, antigen‐presenting cells, and the tumor cells of approximately half of gastric cancers . PD‐L1 is a ligand for the inhibitory T‐cell receptor PD‐1, which induces T‐cell exhaustion, apoptosis, and anergy .…”
Section: Principles Of Checkpoint Blockade Immunotherapymentioning
confidence: 99%